KEAMANAN DAN KENYAMANAN TROTOAR DI TAMAN TINGKIR, KOTA SALATIGA - Yudhistira Adi Nugroho (Architecture Department University of Merdeka Malang, 2018)
A sidewalk is a means for pedestrians which is needed to increase safety and convenience for the society in doing their everyday tasks as an alternative means of transportation. The sidewalk which will be the base of this research are the sidewalks around the Tingkir park area, Salatiga. The purpose of this research is to find out whether or not the sidewalks around Tingkir park are safe and Convenient both in terms of physical, user, and sidewalk utilization. The method which will be used in this research is a combination of evaluative and qualitative methods which refers to quantitative studies. Data is collected via observation, questionnaire, interviews, and literature study. The respondents are selected using nonprobability technique by sampling using accidental sampling and purposive sampling. The number of questionnaire respondents is 60 people. Physical sidewalk data will be analysed using comparative methods. Sa for the questionnaires will be analysed using weighting analysis method. Questionnaire data will later be supported by interview data from the pedestrians. Research suggests that from a physical perspective, the sidewalks around Tingkir park area is regarded as a worthy of being included in the safe and convenient category because it has followed the sidewalk standards set by the government. However, due to misuse of the sidewalk, such as street vendors, and rental of toys, and also the road marking areas are used for illegal parking, the sidewalks at Tingkir park are not save and convenient, misuse of the sidewalks not only effects the safety and smooth circulation of road users, but also effects cleanliness negatively and also disrupts the beauty of the sidewalks at Tingkir park, Salatiga. DOI: https://doi.org/10.26905/mintakat.v19i1.1440